Ethnobotanical survey of medicinal plants traded at Tamu in Sabah urban area - Jurry Foo,; Abdul Latiff Mohamad,; Mustafa Omar,; Ahmad Aldrie Amir, (Institut Alam dan Tamadun Melayu, Universiti Kebangsaan Malaysia, 2016)
Medicinal plants are still important to the livelihood of urban communities in Kota Kinabalu, Sabah. As the main regional growth centre, the rapid development of the city is not a problem for the medicinal plants market to survive. Most of this biomedicine product can be found being sold at the local market which they called as Tamu. Understanding the importance of medicinal plants may help to design appropriate resource management policies in fulfil the needs for urban community. To understand the values of this product to the urban community, identification of the species involved is necessary. This paper present the species of medicinal plant traded in Kota Kinabalu. Survey has been done through observation, interviews and sample collection from eight tamu. In total, 62 species has been collected, while their uses and the usage were described.